2007
DOI: 10.3998/ark.5550190.0009.305
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of enantiomeric spirooxazolines and spirooxazolidines by the regioselective ring closure of (–)-α-pinene-based aminodiols

Abstract: Starting from (1R,2S,3S,5R)-2-benzylaminomethyl-6,6-dimethylbicyclo[3.1.1]heptane-2,3-diol (4) and (1R,2S,3S,5R)-2-aminomethyl-6,6-dimethylbicyclo[3.1.1]heptane-2,3-diol (5), spirooxazolines and spirooxazolidines were prepared. In the reactions of 4 and 5 with alkyl or aryl isothiocyanate, the ring closure proceeded regioselectively and resulted only in spiro derivatives of 2-aryl-and alkyliminooxazolidines 12-17. The primary aminodiol 5 was transformed with ethyl 4-chlorobenzimidate to a spiro-2-(4-chlorophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
2
3
1
Order By: Relevance
“…The structure of 21A was determined by 1 H (whereas the CH-OH gave a dublet in DMSO-d 6 while the CH 2 -OH of 21B could be detected as triplet) and 2D NMR spectroscopic techniques (HMBC). It is important to mention that this regioselectivity is the opposite to that observed in the reaction of aminodiols 13 and 16 with aldehydes (see Scheme 4 and Scheme 5), but it is similar to that observed in our earlier study with pinane-based 3-amino-1,2-diols [41]. During the NMR spectroscopic study of 21A in CDCl 3 for 30 days, an unknown slow ring-ring tautomerization was observed, forming a 1:1 mixture of the two regioisomers 21A and 21B.…”
Section: Synthesis and Transformations Of Pinanebased 2-amino-13-diolssupporting
confidence: 84%
See 1 more Smart Citation
“…The structure of 21A was determined by 1 H (whereas the CH-OH gave a dublet in DMSO-d 6 while the CH 2 -OH of 21B could be detected as triplet) and 2D NMR spectroscopic techniques (HMBC). It is important to mention that this regioselectivity is the opposite to that observed in the reaction of aminodiols 13 and 16 with aldehydes (see Scheme 4 and Scheme 5), but it is similar to that observed in our earlier study with pinane-based 3-amino-1,2-diols [41]. During the NMR spectroscopic study of 21A in CDCl 3 for 30 days, an unknown slow ring-ring tautomerization was observed, forming a 1:1 mixture of the two regioisomers 21A and 21B.…”
Section: Synthesis and Transformations Of Pinanebased 2-amino-13-diolssupporting
confidence: 84%
“…When compound 16 was treated with formaldehyde at room temperature, pinane-fused oxazolidine 17 was obtained regioselectively (Scheme 5), as it was indicated by clear HMBC correlations between the CH 2 of the oxazolidine ring and the anellation carbons, in contrast to the results observed in the case of the regioisomeric 3-amino-1,2-diols, where spiro-oxazolidines formed exclusively [41]. The configuration of oxazolidine 17 was determined by 2D NMR spectroscopic techniques.…”
Section: Synthesis and Transformations Of Pinanebased 2-amino-13-diolsmentioning
confidence: 98%
“…This was indicated by clear HMBC correlations between CH2 of the oxazolidine ring and the anellation carbons. It is in contrast to the results observed in the case of regioisomeric 3-amino-1,2-diols, where spiro-oxazolidines formed exclusively 156 . The structure of 265 and, therefore, the regioselectivity of the reaction were determined by 2D NMR and X-ray techniques.…”
Section: Scheme 31contrasting
confidence: 99%
“…It is important to mention that this regioselectivity is the opposite to that observed in the reaction of aminodiols 11 and 14 with aldehydes (see Schemes 4 and 5), but it is similar to that observed in our earlier study with pinane-based 3-amino-1,2-diols. [40] During the NMR study of 19A in CDCl3 for 30 days, an unknown slow ring-ring tautomerisation was observed, forming a 1:1 mixture of two regioisomers 19A and 19B. Compound 19B could be isolated from the mixture by column chromatography in pure form.…”
Section: Scheme 4: Synthesis Of N-benzyl-2-amino-13-diol 14mentioning
confidence: 99%
“…When 14 was treated with formaldehyde at room temperature, pinane-fused oxazolidine was obtained regioselectively, in contrast to the results observed in the case of regioisomeric 3-amino-1,2-diols, where spiro-oxazolidines formed exclusively. [40] The relative configuration of 15 was determined by 2D NMR technics.…”
Section: Scheme 4: Synthesis Of N-benzyl-2-amino-13-diol 14mentioning
confidence: 99%